Size and shape variation of Hypsipyla grandella Zeller (Lepidoptera: Pyralidae) in two hosts: A morphometric approach (2023)
ABSTRACT: The mahogany shoot borer (Hypsipyla grandella) attacks different Meliaceae species and impedes its plantation. Its biology is poorly known, but some results show a preference for Cedrela odorata L. over Swietenia macrophylla King, which could generate intraspecific variations. We studied the effect of these hosts on H. grandella rightforewing size and shape variation, using a geometric morphometry approach. We collected larvae in planta tions of each host, rose them in seedlings of the same original host and set 13 landmarks on 63 right-forewings. Sexual-shape dimorphism was present and the right-forewings of individuals collected in C. odorata were larger. Removing the allometric effect and comparing magnitude and direction in the plastic responses of the sexualshape dimorphism, we only found differences in the direction. Differences in the right-forewing shape within sexes were present when comparing hosts and removing the allometric effects. Only the right-forewing of males differs between hosts in terms of shape. The differences found could influence the species’ flying system. In dividuals with the larger right-forewings could be more frequent in C. odorata plated areas, with an increased ability for long-distance flights, which is undesired in integrated pest management systems.